First, I want to ask this question. Would r+r+r+r+r equal 5r?

Ok, now onto the simplifications that I'm having trouble with:

1. f - 3f + 2 - f +1

2. -8q + 6 + 5q - 3

3. h + 5h - 3 - 6h

4. 2a- 5(a +1)

I have no clue what I'm doing here. (Headbang)

Printable View

- Jul 6th 2008, 03:57 PMladykcollecting like terms
First, I want to ask this question. Would r+r+r+r+r equal 5r?

Ok, now onto the simplifications that I'm having trouble with:

1. f - 3f + 2 - f +1

2. -8q + 6 + 5q - 3

3. h + 5h - 3 - 6h

4. 2a- 5(a +1)

I have no clue what I'm doing here. (Headbang) - Jul 6th 2008, 04:46 PMDried Monkey
Here are my answers to those questions:

Yes, it would equal 5r.

1. f + 3

2. -3q + 3

3. 3

4. 2a^2 - 5a

I'm not positive about #4. - Jul 6th 2008, 04:52 PMladyk
Is it ok if you showed me how you worked out those answers?

- Jul 6th 2008, 05:39 PMDried Monkey
Sorry, here are my steps:

1. f - 3f + 2 - f +1

= f - (f + f + f) + 2 - f + 1

= f + f + 2 - f + 1

= f + (f - f) + 2 + 1

= f + 2 + 1

= f + 3

2. -8q + 6 + 5q - 3

= (-8q + 5q) + 6 - 3

= -3q + 6 - 3

= -3q + 3

3. h + 5h - 3 - 6h

= 6h - 3 - 6h

= (6h - 6h) - 3

= - 3

4. 2a- 5(a +1)

= 2a - 5a +1

= -3a +1

I guess it's a good thing I redid it showing my steps; #3 and 4 were wrong. - Jul 6th 2008, 05:41 PMtopsquark
- Jul 6th 2008, 05:46 PMDried Monkey
Yeah, that makes more sense. I wasn't sure about that one. Good thing you corrected me.